Analisis Putusan Pengadilan Negeri Pontianak Nomor : 1739 K/Pdt/2016 Mengenai Perusahaan Asuransi yang tidak Membayar Klaim secara Penuh - Gustiani, Rosa; Febriany, Tri Atika; Lestari, Nina Niken (Faculty of Law, Universitas Muhammadiyah Pontianak, 2024)
The high cost of medical care, including hospitalization, medication, and transportation, has led many people to choose health insurance to transfer some of the financial risks caused by the uncertainty of medical events. Risk in insurance is related to the possibility of financial loss. However, despite insurance agreements clearly outlining rights and obligations, insurance companies often fail to fulfill their responsibilities, as evidenced in the Supreme Court of Justice Decision Number 1739 K/Pdt/2016 regarding the rejection of a life insurance claim by PT. BNI LIFE INSURANCE. This study aims to analyze the legal consequences of discrepancies in claim payments and the factors that cause them. Using a sociological and descriptive legal research method, the study shows that disputes can be resolved through negotiation, arbitration, or litigation, depending on the terms of the insurance policy. The claim denial occurred due to the policyholder's dishonesty in disclosing their health condition during the policy registration, which violated the principles of transparency and honesty in insurance.